2009
DOI: 10.1590/s0034-89102009000800006
|View full text |Cite
|
Sign up to set email alerts
|

Satisfação dos usuários dos centros de atenção psicossocial da região Sul do Brasil

Abstract: OBJECTIVE:To evaluate user satisfaction with psychosocial healthcare services. METHODS:Qualitative and quantitative study conducted in psychosocial healthcare services in the states of Paraná, Santa Catarina and Rio Grande do Sul, Southern Brazil, in 2006. The study combined quantitative and qualitative methods. Quantitative epidemiological data from a cross-sectional study including 1,162 users of 30 psychosocial healthcare services was used. The instrument used to evaluate users' satisfaction was the Brazili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
0
46

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 4 publications
6
32
0
46
Order By: Relevance
“…These results concur with those of studies performed at mental health services in other counties (20)(21)(22) .…”
Section: Discussionsupporting
confidence: 91%
“…These results concur with those of studies performed at mental health services in other counties (20)(21)(22) .…”
Section: Discussionsupporting
confidence: 91%
“…The results concerning the patient sample that indicate moderate overall satisfaction with the service contradict those of international (Blenkiron & Hammill, 2003;Gani et al, 2011;Holikatti et al, 2012) and Brazilian studies (Heckert et al, 2006;Kantorski et al, 2009;, which report high levels of satisfaction. One potential explanation for this difference, especially in comparison to Brazilian studies, may be related to the type of service assessed.…”
Section: Discussionmentioning
confidence: 56%
“…The family caregivers were satisfied with information received; however, 58% of the patients were moderately satisfied or dissatisfied with this aspect. Other studies (Kantorski et al, 2009; also found low levels of satisfaction among patients in regard to information received. According to Ruggeri (2010), the quantity and quality of information provided to patients is a predictor of the level of satisfaction.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations